Variability of the structural characters of the bark in the laticiferous system of the juvenile Hevea seedlings - Gonçalves, Paulo de Souza; Martins, Antonio Lúcio Mello; Bortoletto, Nelson; Utida, Rita de Cássia (Pesquisa Agropecuaria Brasileira, 1995)
Studies of variability and repeatability for characters of the laticiferous system of the bark in 76 three-year old seedlings of rubber tree [Hevea brasiliensis (Willd. ex. Adr. de Juss.) Müell Arg.] were undertaken. The studied characters were bark thickness (EC) total number of latex vessel rings (NA), diameter of latex vessel rings (DIA), density of latex vessels per 5 mm per ring averaged over all rings (DD) and average distance between consecutive latex vessel rings (DMV). Based on the analysis of variance, coefficient of repeatability and genetic gains were estimated for each character for each two, three and four different height samples taken from the stem of each seedling. The highest average repeatability values were p = 0.73 and p = 0.93 for DMV and EC, respectively. These highest genetic advances were obtained for EC and NA with four (Gs = 22.51%) and five (Gs = 11.35%) samples, respectively. Based on the results it was concluded that repeatability and the high percentual of genetic gain obtained of three bark samples from different heights showed a better progress in the selection.